1998
DOI: 10.3109/10731199809117477
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Heat Treatment Step Used in the Production of Diaspirln Crosslinked Hemoglobin (DCLHb™) For Viral Inactivation

Abstract: A series of experiments was performed to assess the ability of the heat treatment step used in the manufacture of diaspirin crosslinked hemoglobin (DCLHb) to inactivate viruses. In-process solutions (reaction mixtures after the crosslinking process) from six different manufacturing lots were used as test media in a 1:680 scaled down system in which the key process parameters used in the large scale production were duplicated. The inactivation of five different viruses (Bovine Viral Diarrhea Virus, Pseudorabies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Terminal sterilization of Hb products is usually achieved by filtration. Some cross-linked materials, being more stable, have been pasteurized. Complete removal of endotoxins from recombinant Hb produced in pathogenic bacteria is also a challenge …”
Section: Ensuring Sterility Absence Of Endotoxinmentioning
confidence: 99%
“…Terminal sterilization of Hb products is usually achieved by filtration. Some cross-linked materials, being more stable, have been pasteurized. Complete removal of endotoxins from recombinant Hb produced in pathogenic bacteria is also a challenge …”
Section: Ensuring Sterility Absence Of Endotoxinmentioning
confidence: 99%
“…Hb S-nitrosylation (by the mechanisms outlined in reactions [5][6][7][8] is competitive with the dioxygenation reaction (reaction 3) and accounts for a physiological concentration of 10 -7 -10 -5.5 M SNO-Hb in human blood (87,119,123,147,164). Although the preponderant role of O 2 (vs. other electron acceptors) in reaction 5 is still under debate (62,109), crystallographic studies have unequivocally demonstrated both the existence of SNO-Hb and the allosteric control of its generation (22,23).…”
Section: Loading Hb With No Bioactivitymentioning
confidence: 99%
“…Allostery can be further manipulated to align the cell-free Hb's O 2 affinity (which is higher than that of intra-RBC Hb) to physiological values compatible with its clinical use (125,155). Furthermore, various conjugates and cross-linked tetrameric Hb derivatives potently prevent dimerassociated toxicity of cell-free Hb (1) and may prolong Hb shelf-life (6). O 2 affinity is augmented in cell-free Hb not only secondary to dimer formation but also because of the loss of erythrocytic allosteric regulators, such as 2,3-DPG; this difference is important in investigational comparison of cell-free and erythrocytic Hb-NO biology as well as in blood substitute development.…”
Section: Excess Morbidity and Mortality With Rbc Transfusionmentioning
confidence: 99%
“…General characteristics of the product were published in descriptions of the process, both by Baxter [33, 34, 37, 44, 53]and LAIR [30, 31, 32, 45, 54]. …”
Section: Characterizationmentioning
confidence: 99%
“…The reaction mixture was heated to 60°C for 10 h at pH 7.5, and the less stable unreacted tetramers precipitated out of solution. Although several methods of virus removal and inactivation were evaluated by Baxter [41], this increased stability was exploited to introduce a heat viral inactivation step [42, 43, 44, 45]. The final product was formulated in either Ringer’s acetate, Ringer’s lactate or other physiologic buffer solutions for biological testing.…”
Section: Productionmentioning
confidence: 99%